2007
DOI: 10.1289/ehp.9024
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Etiologies of Childhood Leukemia: Plausibility and Challenges to Proof

Abstract: Infections as well as environmental exposures are proposed determinants of childhood acute lymphoblastic leukemia (ALL), particularly common precursor B-cell ALL (cALL). Lines of investigation test hypotheses that cALL is a rarer result of common infection, that it results from uncommon infection, or that it ensues from abnormal immune development; perhaps it requires a preceding prenatal or early childhood insult. Ideally, studies should document that particular infections precede leukemia and induce malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…Further support is drawn from the population-mixing theory that an excess of childhood leukemia has been found in rural, potentially immunologically naive, populations that have undergone an influx of permanent residents. [8][9][10][11][12] Breast milk is a total food meant to exclusively supply all the nutritional needs of infants. Current recommendations of leading health organizations, including the American Academy of Pediatrics 13 and the World Health Organization, 14 state that "infants should be exclusively breastfed for the first six months of life to achieve optimal growth, development and health.…”
mentioning
confidence: 99%
“…Further support is drawn from the population-mixing theory that an excess of childhood leukemia has been found in rural, potentially immunologically naive, populations that have undergone an influx of permanent residents. [8][9][10][11][12] Breast milk is a total food meant to exclusively supply all the nutritional needs of infants. Current recommendations of leading health organizations, including the American Academy of Pediatrics 13 and the World Health Organization, 14 state that "infants should be exclusively breastfed for the first six months of life to achieve optimal growth, development and health.…”
mentioning
confidence: 99%
“…1 However, unlike leukemia in some animals 2 and HTLV-associated adult T-cell leukemia, 3 studies have not been able to show a direct pathologic involvement of specific infection(s) for leukemia in children. 4 It has been suggested that for childhood leukemia, particularly for precursor B-cell acute lymphoblastic leukemia (ALL), a delay in exposure to common childhood infections leaves the immune network undermodulated, and subsequent exposure to infections results in an unfavorable immune response; specifically, a proliferative advantage to preleukemia cells. 5 This "delayed infection" hypothesis suggests that exposure to infections or other immune-modulatory factors early in life may result in a protective effect against childhood ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, early infections have a protective effect in ALL by promoting the physiological maturation of the immune system, whereas late infections promote an excessive proliferation of the lymphocytes (McNally and Eden, 2004;Menegaux et al, 2004;Greaves, 2006;O'Connor and Boneva, 2007).…”
mentioning
confidence: 99%